Evaluation of the impact of factors on loan pricing - Наталия Горелая (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2016)
Natalia Gorelyaya - National Research University "Higher School of Economics".Email: ngorelaya@hse.ruThe process of determining the loan price includes assessment and accounting for a wide range of factors, such as price of borrowed funds and other costs of the bank, associated banking risks, competition within the sector, character of the borrower and his relationship with the bank and so on. Thereby there is a great scope for investigation.This paper examines the impact of selected loan characteristics (terms, purpose, amount and borrowers’ creditworthiness) on the loan price. Applying regression analysis based on a lender provided dataset covering the period from the beginning of 2007 until the mid-2015, this paper is able to differentiate these effects with respect to distribution of mortgage loan pricing and other loan pricing (consumer and corporate). The coefficient of collateral is not statistically significant. Funding rate is not statistically significant for both cases. The regression results indicate that loan characteristics such as amount, duration of the loan, lower level of borrowers’ creditworthiness and paradoxically collateral increase price of mortgage loan. For other loans, including in credit portfolio, the finding suggest that consumer loans with medium or long duration and lower level of borrowers’ creditworthiness receive a higher price. The increase in amount of debt, another type of borrowers (corporate loans) and the mechanism of lending (credit line) will cause reduction in a loan price. The coefficients of collateral and funding rate are not statistically significant.The finding results from this paper may help lenders and borrowers better understand the underlying pricing process.